The protective effects of melatonin postconditioning in cerebral ischemia may be mediated through the modulation of FUNDC1 and Bnip3 levels - Aslan, Gulnur; Bulmus, Ozgur; Tuzcu, Mehmet; Gokdere, Ebru; Sahna, Kezban Can; Şahin, Kazım; Sahna, Engin (Taylor & Francis Ltd, 2026)
ObjectiveThe regulation of mitochondrial bioenergetics - as one of the endogenous defense mechanisms against ischemia-reperfusion (IR) injury - has been considered promising. This study aimed to determine which mitophagy-related signaling pathways (parkin, Bnip3, or FUNDC1) mediate the protective effects of postconditioning (PostC) and melatonin, both of which enhance the intrinsic defense capacity of cerebral tissue. In addition, microRNA-137 and microRNA-145, as well as serum asprosin, a novel glucogenic adipokine, levels were analyzed in cerebral IR injury.MethodRats were divided into four groups: control (sham), IR, IR+PostC and IR+Mel(n:10). After 90 minutes of occlusion, PostC was performed at the onset of reperfusion in three cycles of 30-sec reperfusion, followed by 10-sec ischemia. Results: All parameters involved in mitophagy pathways increased with IR in cerebral cortex, and serum asprosin level decreased. Parkin and PINK1 levels did not change due to the treatments, while the FUNDC1 and Bnip3 levels decreased and serum asprosin levels increased significantly compared to IR. MicroRNA-137 and microRNA-145 decreased, although treatment partially restored the levels of these microRNAs.ConclusionIncreased expressions of parkin/PINK1, FUNDC1 and Bnip3 may suggest that all mitophagy pathways are activated by cerebral IR. Melatonin PostC may protect the cerebral tissue by inhibiting BN & Idot;P3- and FUNDC1-mediated mitophagy.
Keywords: Ischemic postconditioning; melatonin; asprosin; Bnip3; FUNDC1; microRNA-137 and-145